1995
DOI: 10.1016/0895-7061(95)00182-o
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of calcium metabolism and of parathyroid function in primary aldosteronism, and their reversal by spironolactone or by surgical removal of aldosterone-producing adenomas

Abstract: In order to investigate the possible existence of abnormal calcium metabolism and parathyroid function in primary aldosteronism (PA), we have compared the calcium/parathyroid hormone (PTH) profile of patients with PA with the profile of healthy normotensive subjects and of patients with essential hypertension (EH). Furthermore, we have evaluated the effects of spironolactone and the surgical removal of aldosterone-producing adenomas on the calcium/PTH profile in the PA patients. Four groups of 10 subjects each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
109
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(130 citation statements)
references
References 52 publications
10
109
0
1
Order By: Relevance
“…Moreover, the fractional excretion of Ca 2ϩ was higher during GA compared with baseline, indicating that the increase in calciuria was a consequence of decreased tubular reabsorption. Thus, the present observation is consistent with the reduced concentration of serum ionized Ca 2ϩ and increased urinary Ca 2ϩ excretion reported in patients with primary aldosteronism (13,14).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the fractional excretion of Ca 2ϩ was higher during GA compared with baseline, indicating that the increase in calciuria was a consequence of decreased tubular reabsorption. Thus, the present observation is consistent with the reduced concentration of serum ionized Ca 2ϩ and increased urinary Ca 2ϩ excretion reported in patients with primary aldosteronism (13,14).…”
Section: Discussionsupporting
confidence: 92%
“…The higher urinary Ca 2ϩ excretion observed during inhibi- tion of 11␤HSD2 is consistent with the increased calciuria observed in both animals (27) and humans (28) after long-term mineralocorticoid administration, as well as with the higher Ca 2ϩ excretion reported in patients with primary aldosteronism compared with that in normotensive control subjects (14,29). However, this increase in urinary Ca 2ϩ excretion associated with mineralocorticoid excess does not seem due to direct effects of aldosterone.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…They reported that serum calcium levels tend to be low, and plasma PTH levels tend to be high in patients with primary aldosteronism. The abnormalities were corrected after administration of spironolactone or surgical treatment (15), suggesting that primary aldosteronism is associated with mild secondary hyperparathyroidism. Coupled with these observations, serum calcium levels should be interpreted with caution in patients with primary aldosteronism, because hypercalcemia may be masked in the presence of aldosterone excess.…”
Section: Discussionmentioning
confidence: 97%
“…Both changes may lead to lowered serum calcium levels. Of relevance are studies by Resnick and Laragh (14), and by Rossi et al (15). They reported that serum calcium levels tend to be low, and plasma PTH levels tend to be high in patients with primary aldosteronism.…”
Section: Discussionmentioning
confidence: 99%